The relationship between inotropic support therapy and central partial pressure of venous-arterial carbon dioxide after cardiopulmonary bypass - (:unkn) unknown (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2019)
Background: This study aims to investigate the effects of partial pressure of venous-arterial carbon dioxide changes in the early period after cardiopulmonary bypass in patients who did or did not receive inotropic support therapy and the effect of these changes on tissue perfusion. Methods: A total of 100 consecutive patients (70 males, 30 females; mean age 61.8 +/- 2.3 years; range, 20 to 75 years) who underwent open heart surgery were divided into two groups as those who did not receive any inotropic agent (group 1, n=50) and those who received at least one inotropic agent (group 2, n=50) during the early postoperative period. Heart rate, blood oxygen saturation level, mean arterial pressure, central venous pressure and urine volume, lactate and base excess levels were recorded during the postoperative first 24 hours. At the same timeframe, partial pressure of venous-arterial carbon dioxide level was calculated from central venous and peripheral blood samples. Results: In both groups, partial pressure of venous-arterial carbon dioxide were significantly higher in the postoperative fourth hour compared with basal values. This significant difference continued for the postoperative first 24 hours. Partial pressure of venous-arterial carbon dioxide in group 2 was significantly higher at the 12th-hour measurement (p=0.002). Lactate levels at zeroth and eighth hours were significantly higher in group 2 (p=0.012 and p=0.017, respectively). Fourth-hour urine excretion volumes were significantly lower in group 1 (p=0.010). Mean arterial pressure at zeroth, 12th and 20th hours was significantly higher in group 2 (p=0.001, p=0.016, and p=0.027, respectively). At the eighth-hour measurement, a positive weak relationship was detected between partial pressure of venous-arterial carbon dioxide and lactate levels (r=0.253 and p=0.033). Conclusion: This study demonstrated that partial pressure of venous-arterial carbon dioxide increased in the first few hours and remained to be high for 24 hours after cardiopulmonary bypass independently of the use of inotropic support. However, in the postoperative period, even after lactate and base excess levels return to baseline values, partial pressure of venous-arterial carbon dioxide may continue to remain at high values, which may indicate impaired perfusion in some tissues.
Keywords: Cardiopulmonary bypass; tissue perfusion; venous-arterial carbon dioxide pressure; ADULT CARDIAC-SURGERY; OXYGEN-SATURATION; TISSUE PERFUSION; DIFFERENCE; LACTATE; GOAL; PREDICTOR; GRADIENT; OUTPUT